2018
DOI: 10.1039/c8nj01410h
|View full text |Cite
|
Sign up to set email alerts
|

Solar light active plasmonic Au@TiO2 nanocomposite with superior photocatalytic performance for H2 production and pollutant degradation

Abstract: Spherically shaped plasmonic Au nanoparticles (NPs) of size 10 nm (±4 nm) have been decorated on TiO2 NPs for the synthesis of Au@TiO2 composites via an aqueous sol–gel method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 69 publications
3
41
0
1
Order By: Relevance
“…The band gaps shown in Figure 3b are smaller than that of the 10 nm TiO 2 film with increases in the thickness of the TiO 2 . The bandgap reduced no further when the TiO 2 thickness was greater than the size of the Ag nanoparticles [45].…”
Section: Resultsmentioning
confidence: 99%
“…The band gaps shown in Figure 3b are smaller than that of the 10 nm TiO 2 film with increases in the thickness of the TiO 2 . The bandgap reduced no further when the TiO 2 thickness was greater than the size of the Ag nanoparticles [45].…”
Section: Resultsmentioning
confidence: 99%
“…Several researchers have focused on obtaining a heterostructure that improves interaction between the nanoparticles and the semiconductor oxide in order to enhance photocatalytic activity. Heterogeneous photocatalysis using AuNPs has generally been employed for the degradation of dyes [154][155][156], organic synthesis [157][158][159], and the generation of energy sources, particularly the production of hydrogen and methane [160][161][162][163].…”
Section: Heterogeneous Catalysismentioning
confidence: 99%
“…† In IR spectra, a sharp band centred at 500-750 cm À1 was attributed to metal oxygen (Ti-O) bond and bridging Ti-O-Ti or Ti-O-Cr stretching modes. [54][55][56][57][58][59][60][61][62] The IR signal in the range of 400-1250 cm À1 was Fig. 4 (A) Nitrogen physisorption isotherms of (a) undoped TiO 2 and (b) 5% Cr-TiO 2 calcined at 400 C. Inset: BJH pore size distribution curves of (a) undoped TiO 2 and (b) 5% Cr-TiO 2 at 400 C. (B) N 2 sorption isotherm of 5% Cr-TiO 2 recovered after the third cycle.…”
Section: Ft-ir and Raman Spectra Of Cr-tio 2 Catalystsmentioning
confidence: 99%
“…38 However our group has successfully demonstrated that an aqueous titanium peroxide-based modied sol-gel method is suitable for synthesizing N-and transition-metal-doped TiO 2 thin lm and powder photocatalysts. [49][50][51][52][53][54][55][56] A series of doped TiO 2 photocatalysts have been synthesized using this technique and undoped and doped TiO 2 have been applied to organic pollutant degradation and H 2 O splitting into H 2 under UV and visible light, especially under naturally available energy sources such as sunlight. In most reports, Crdoped TiO 2 has been used for organic pollutant degradation, but the application of Cr-TiO 2 to the degradation of spent wash, an industrial waste from sugar-based alcohol distilleries, has yet to be reported.…”
Section: Introductionmentioning
confidence: 99%